DOI: 10.17077/etd.zc7140w7
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative assessment of infraorbital morphology in Homo

Abstract: Features of the infraorbital region, such as infraorbital surface topography, infraorbital surface orientation, and curvature of the zygomaticoalveolar crest, have long played a prominent role in phylogenetic analyses of Homo. However, there is currently considerable debate regarding the phylogenetic reliability of infraorbital characters, as numerous researchers have questioned the degree to which these features are morphologically independent of one another and facial size. These questions stem largely from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 241 publications
(637 reference statements)
1
2
0
Order By: Relevance
“…Our previous study found more laterally extended sinuses were clearly associated with aspects of lateral facial morphology, most notably, anteriorly projecting zygomatics. However, as we noted in our previous study, exceedingly anteriorly projecting zygomatics are commonly considered a distinctive characteristic of Asian and Asian‐derived populations (Woo and Morant, ; Howells, ; Hanihara, ; Maddux, ; Evteev et al, ). Because it was our Siberian/Arctic circumpolar sample that exhibited more laterally extending maxillary sinuses, we hypothesized that the association between lateral sinus extension and anterior zygomatic position might have been driven by the shared Asian ancestry of our circumpolar sample.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Our previous study found more laterally extended sinuses were clearly associated with aspects of lateral facial morphology, most notably, anteriorly projecting zygomatics. However, as we noted in our previous study, exceedingly anteriorly projecting zygomatics are commonly considered a distinctive characteristic of Asian and Asian‐derived populations (Woo and Morant, ; Howells, ; Hanihara, ; Maddux, ; Evteev et al, ). Because it was our Siberian/Arctic circumpolar sample that exhibited more laterally extending maxillary sinuses, we hypothesized that the association between lateral sinus extension and anterior zygomatic position might have been driven by the shared Asian ancestry of our circumpolar sample.…”
Section: Discussionsupporting
confidence: 51%
“…As previously noted by Zollikofer et al (), fossil hominins with large zygomaticomaxillary interfaces typically exhibit maxillary sinuses that extend laterally to a considerable degree (in some cases excavating beyond the zygomaxillary suture). Unfortunately, the human fossil record is lacking in adult archaic (i.e., non‐ Homo sapiens ) specimens with relatively small zygomaticomaxillary interfaces (Pope, ; Maddux, ; Freidline et al, ), thus limiting potential comparisons. Still, it is worth noting that several studies of facial ontogeny in fossil Homo (Minugh‐Purvis, ; Maureille and Bar, ; Freidline et al, ) indicate that the relatively large zygomaticomaxillary proportions of archaic humans appeared early in post‐natal development, suggesting that these individuals would have likely had ample space for lateral sinus pneumatization to occur during growth and development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation